DISTRIBUTION OF PARTICULAR AWASSI GENETIC LINES TO ADDRESS JORDAN'S FOOD SAFETY CHALLENGE - Jawasreh, K.; Albreiki, M.; Al-Brzinji, Y. M.; Al-Amareen, A.; Al-Rawashdeh, I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study aimed to enhance food security in Jordan by improving meat quantity and quality in Awassi sheep through introducing two economical genomic mutations; FecB and CLPG. In this study, a group of 209 Awassi ewes were involved in the study where 10 heads were distributed to each collaborated farmer, then Half of the  ewes were inseminated with mutations Carrier’s rams, while the other half was inseminated with rams carrying the CLPG mutation, After the lambing season, a genomic DNA extraction and genotyping process (FRLP) for the newborns was conducted and revealed successful introgression of the mutations, resulting in lambs carrying either the FecB or CLPG mutations. Our results showed the successful introduction of the FecB and CLPG mutations in Awassi sheep, with a considerable number of lambs carrying the mutation, in Jordan the frequencies of the mutations were almost zero but now and after introducing the carrier rams to farmer’s fields it has been increased to 0.41 (as heterozygous FecB genotype) and 0.50 for that CLPG heterozygous genotype (in the supported population). Ewes who were in the first parity their Prolificacy was elevated up to 2.5 lambs/ of those holds the FecB mutation. The new introduction of the mutation to farmer’s fields will contribute directly to the livelihood of the farmers and enhancing food security in Jordan.